1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of an Interferon‐Inducible Protein Encoded by Gene 203 from the Gene 200 Cluster

Abstract: We report here the complete coding sequence of a 203 cDNA, a member of the interferon-inducible Ifi 200 gene family. By combining reverse-transcriptase PCR and rapid amplification of cDNA ends (RACE) techniques we have obtained a 3.8-kb cDNA corresponding to a 203 mRNA. When used as a probe in northern analysis, its 3' segment hybridized to a 3.8-kb interferon-inducible mRNA, whereas the S'-end additionally hybridized to a less abundant interferon-inducible 1 .8-kb mRNA. Nucleotide sequence analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The size of the spacer region in IFI 16 is regulated by mRNA splicing and can contain one, two, or three copies of a highly conserved 56-amino-acid S/T/P domain encoded by distinct exons (23). In contrast, MNDA, AIM-2, p203, and D3 contain only one 200-amino-acid domain (3,17,18,20). The amino acid composition of the A domains expressed in different HIN-200 proteins is highly conserved, as are the B domains expressed in different family members.…”
Section: Structure and Expression Of The Hin-200 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the spacer region in IFI 16 is regulated by mRNA splicing and can contain one, two, or three copies of a highly conserved 56-amino-acid S/T/P domain encoded by distinct exons (23). In contrast, MNDA, AIM-2, p203, and D3 contain only one 200-amino-acid domain (3,17,18,20). The amino acid composition of the A domains expressed in different HIN-200 proteins is highly conserved, as are the B domains expressed in different family members.…”
Section: Structure and Expression Of The Hin-200 Proteinsmentioning
confidence: 99%
“…The HIN-200 family of proteins consists of a number of highly homologous human and murine proteins with similar primary amino acid sequences and biological characteristics. The human HIN-200 family members include IFI 16 (39), the myeloid nuclear differentiation antigen (MNDA) (2,18), and AIM-2 (absent in melanoma) (17), while the mouse HIN-200 family members include p202 (3), p203 (20), p204 (3), and D3 (38). There are a number of reviews that elegantly outline the biochemical characteristics of these proteins and their patterns of expression (15,27,30).…”
mentioning
confidence: 99%
“…Although these results indicate that p204 is probably involved in the control of the cell cycle throughout the pRB-pathway, they do not shed light on the mechanisms it employs. For this purpose in a previous study we generated both p204 deletion mutants lacking one of the two domains, and chimeric proteins bearing the a domain from p204 and the b domain from p203, another member of the I®200 family (Gribaudo et al, 1997(Gribaudo et al, , 1999. The results of transfection in sensitive cells clearly demonstrated that to exert its antiproliferative activity, accumulate cells at the G1/S border, and inhibit the E2F-mediated transcriptional activity p204 needs both domains.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite few well-established examples, the exact function of the IFN-induced proteins that are ultimately the mediators of their biological activity are still quite unknown [3]. One protein family (p200) consists of at least four members designated p202, p203, p204, and D3, encoded by a cluster of genes located in the q21-23 region of mouse chromosome 1 (Ifi 200 genes) [4][5][6][7][8][9]. All these proteins share one or two partially conserved 200-amino acid segments, designated as the type a and the type b domain.…”
Section: Introductionmentioning
confidence: 99%